Relationship between fermentation behavior, measured with a 3D vision Structured Light technique, and the internal structure of bread. (February 2015) - Verdú, Samuel; Ivorra, Eugenio; Sánchez, Antonio J.; Barat, Jose M.; Grau, Raúl
Highlights: Relationship between Structured Light 3D technique and internal structure of dough. Differences between two different wheat flour samples were analyzed. Expansion of bubbles of dough during fermentation process influenced the 3D information. Information obtained by technique is able to characterize growth rate of bubbles. Abstract: The bread-making process is a set of operations where could be relevant to use monitoring methods. Specifically, the fermentation phase is a crucial step in which the quality of the product can be affected. Several methods have been developed to monitor this stage based on different technologies. The aim of this study was to analyze and obtain information about the internal structure of bread dough during the fermentation process using a 3D vision system based on Structured Light (SL). The differences about fermentation behavior of two wheat flours classified as "high strength flour" by company providing were studied. The parameters of the internal structure of the baked product (final bubble size and their population density) were analyzed with 2D image segmentation. An important correlation ( r  = 0.865) was observed between the 3D and 2D information, specifically between the transversal area and height (3D), and final bubble size and number of bubbles (2D). Although at the end of the dough fermentation process ( Tf ) the area ( A ) and maximum height ( H ) were different, the relationship between both parameters were similar, reaching a similar bubble size as a consequence of coalescence phenomena, independent of the bubble growth rate. This could be a base for the development of prediction models and devices to monitor the fermentation phase of the bread-making process.